A Child with Local Lipohypertrophy following Recombinant Human Growth Hormone Administration - Ilan J. N. Koppen; Roel Bakx; Chris C. de Kruiff; A. S. Paul van Trotsenburg (Case Reports in Pediatrics)
Local lipohypertrophy due to recombinant human growth hormone (rhGH) administration is a rare phenomenon. Here, we report a case of an 11-year-old girl who presented with a paraumbilical swelling, approximately one year after the start of rhGH treatment for short stature due to the presumed diagnosis of partial growth hormone insensitivity. Ultrasound imaging revealed an asymmetric distribution of subcutaneous fat tissue at the rhGH administration site, indicating local lipohypertrophy. After sparing her routine injection site and alternating other sites, the swelling disappeared within 6 months. Although the precise cause of local lipohypertrophy resulting from rhGH administration is still unclear, it might be related to the presumed diagnosis of partial growth hormone insensitivity.